STRATEGI PEMASARAN DALAM MENINGKATKAN HUNIAN KAMAR DI HOMESTAY RUMAH GADANG SUNGAI ANGEK, SIMARASOK, KABUPATEN AGAM, SUMATERA BARAT - Rozi Yuliani; Moch. Abdi (Ensiklopedia of Journal, 2023)
This study aims to determine the strengths, weaknesses, opportunities and threats of marketing implementation in increasing room occupancy rates as well as to determine the application of online marketing in increasing room occupancy rates. Methods of data collection in the form of observation, interviews, questionnaires, and documentation. The sampling technique was in the form of purposive sampling, namely as many as 3 respondents. The analysis technique used is the IFAS (Internal Factors Analysis Summary) Matrix, the EFAS (External Factors Analysis Summary) Matrix, the IE (Internal-External) Matrix, the SWOT Matrix, and qualitative descriptive analysis. The results of the study show that there are several internal and external factors that influence the implementation of online marketing run by Rumah Gadang Homestay. Based on the results of the IFAS matrix analysis, there are 5 indicators that are strengths with 3 indicators that are still weaknesses in the Rumah Gadang homestay. The calculation of the EFAS matrix shows the results of indicators that become opportunities as many as 5 with 3 indicators that can become threats. The results of the IE matrix research put the company in a Growth position (cell V). While the results of research using the SWOT matrix produce 14 alternative strategies that can be used to increase room occupancy rates, which consist of SW, ST, WO, and WT strategies respectively.